A new species of the hermit crab genus Pagurus Fabricius, 1775 (Crustacea: Decapoda: Anomura: Paguridae) from shallow coastal waters in Japan, with a checklist of the East Asian species of the genus - Komai, Tomoyuki; Saito, Yuma; Myorin, Eiji (Zootaxa, 2015)
A new species of hermit crab of the family Paguridae, Pagurus rectidactylus, is described and illustrated on the basis of material from inshore waters in the Seto Inland Sea and the Sea of Japan. It appears closest to P. quinquelineatus Komai, 2003, also known from Japan, but is easily distinguished from the latter by the dactylus of the right cheliped almost unarmed or armed only with a few tiny spines or tubercles, instead of dorsal and dorsomesial rows of conspicuous spines, and the more elongate and slender ambulatory legs with more numerous ventral corneous spines on dactyli and propodi. Housing is also different between the two species: the new species exclusively inhabits carcinoecia formed by a hydrozoan Stylactaria misakiensis (Iwasa, 1934), whereas P. quinquelineatus uses gastropod shells without association with coelenterates. A checklist of East Asian (Japanese Archipelago to Taiwan Island, Far Eastern Russia to northern China) species of Pagurus along with general geographical distributions is presented.